Reduction of lift-off effects for pulsed eddy current NDT - Tian, Gui Yun; Sophian, Ali (Elsevier, 2005)
The lift-off effect is commonly known to be one of the main obstacles for effective eddy current NDT testing as it can easily mask defect signals. Pulsed eddy current techniques, which are believed to be potentially rich of information, are also sensitive to the effect. An approach using normalisation and two reference signals to reduce the lift-off problem with pulsed eddy current techniques is proposed. Experimental testing on the proposed technique and results are presented in this report. Results show that significant reduction in the effect has been achieved mainly in metal loss and sub-surface slot inspection. The technique can also be applied for measurement of metal thickness beneath non-conductive coatings, microstructure, strain/stress measurement, where the output is sensitive to the lift-off effect.